2015
DOI: 10.3390/molecules200610131
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Method for Generating Arynes from ortho-Silylaryl Triflates: Activation by Cesium Carbonate in the Presence of a Crown Ether

Abstract: An alternative method for generating arynes from ortho-silylaryl triflates using cesium carbonate and 18-crown-6 is reported. The method was efficiently applied to a variety of reactions between several arynes and arynophiles. We also demonstrated that the efficiency of aryne generation is significantly affected by the alkali metal countercation of the carbonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…21 However, in 2015 Hosoya and co-workers reported that common ortho-silylaryl triflates 20 could also be activated in the absence of fluoride, instead using mild base, such as Cs2CO3, and a crown ether to couple a range of arynes with various arynophiles (Scheme 5a). 22 Similarly, in 2015, Wang and co-workers found that the analogous ortho-silylaryl…”
Section: 2-difunctionalised Arene Precursorsmentioning
confidence: 96%
See 1 more Smart Citation
“…21 However, in 2015 Hosoya and co-workers reported that common ortho-silylaryl triflates 20 could also be activated in the absence of fluoride, instead using mild base, such as Cs2CO3, and a crown ether to couple a range of arynes with various arynophiles (Scheme 5a). 22 Similarly, in 2015, Wang and co-workers found that the analogous ortho-silylaryl…”
Section: 2-difunctionalised Arene Precursorsmentioning
confidence: 96%
“…Please do not adjust margins Please do not adjust margins Scheme 5 Cs2CO3 as an activator for aryne generation. 22,23 fluorosulfates 27 could also perform as efficient aryne precursors upon the addition of Cs2CO3 and 18-crown-6 (Scheme 5b). 23 Treatment of substituted fluorosulfate precursors 27 with benzyl azide 28 yielded the corresponding benzotriazoles 29 from the Huisgen cyclisation in good to excellent yields.…”
Section: 2-difunctionalised Arene Precursorsmentioning
confidence: 99%
“…16 In addition, we recently developed a fluoride-free method using cesium carbonate and a crown ether to generate arynes from ortho-silylaryl triflates at room temperature ( Figure 2E). 17 Furthermore, we have recently developed a facile method to diversify the simple ortho-silylaryl triflates by utilizing an Ircatalyzed regioselective CH borylation reaction (Scheme 1). 18 Thus, a variety of multisubstituted ortho-silylaryl triflates were easily prepared with a borylated ortho-silylaryl triflate using reactions such as SuzukiMiyaura cross-coupling reaction, a Rhcatalyzed 1,4-addition, halogenation, and azidation.…”
Section: Precursors and Activatorsmentioning
confidence: 99%
“…An otable difference between this methodology and similar transformations involving silyltriflates is that the reaction proceeds in the absence of an activating reagent such as afluoride source or exogenous base. [18] Nitrones have been reported to interact appreciably with Lewis acids, [19] and since multiple equivalents are required we propose that the first is used sacrificially to induce the desired elimination. [20] This would reveal the putative nitroalkyne intermediate, which we propose rapidly undergoes the observed [3+ +2] cycloaddition (Figure 1).…”
mentioning
confidence: 99%